1990
DOI: 10.1016/0014-5793(90)81472-z
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine specifically stimulates plasma membrane H+‐ATPase from corn roots

Abstract: The plasma membrane H+‐ATPase activity from corn seedling roots is shown to be stimulated 3‐ to 4‐fold by the addition of lysophosphatidylcholine (lysoPC). This effect clearly differs from that of other detergents by both the magnitude and the absence of inhibition at higher concentrations. LysoPC decreases the apparent K m for MgATP, increases V max of the ATPase reaction but does not change its pH optimum. On the contrary, the acid phosphatase activity associated with plasma membranes is not influenced by ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
4
10
0
Order By: Relevance
“…This inhibition was also observed by Pedchenko et al (1990), who used lyso-PC/protein ratios of 5 to 12.5. A distinct lyso-PC Lanfermeijer and Prin:;Plant Physiol.…”
Section: Kinetics Of Native and Fc-stimulated Atpase Activitysupporting
confidence: 73%
“…This inhibition was also observed by Pedchenko et al (1990), who used lyso-PC/protein ratios of 5 to 12.5. A distinct lyso-PC Lanfermeijer and Prin:;Plant Physiol.…”
Section: Kinetics Of Native and Fc-stimulated Atpase Activitysupporting
confidence: 73%
“…The activity decreased with an increase in the length of the fatty acyl chain and in the degree of unsaturation of fatty acid (Hernandez et al, 2002;Kasamo, 2003, Martz et al, 2006. Lysophosphatidylcholine (a natural detergent produced from phosphatidylcholine by phospholipase A 2 ) increased the plasma membrane H + -ATPase activity (Pedechenko et al, 1990, Regenberg et al, 1995. It was found that lysophosphatidylcholine binds to the Cterminal region of the protein and by displacing the autoinhibitory domain leads to increase of ATPase activity.…”
Section: Regulation By Membrane Environmentmentioning
confidence: 99%
“…In a yeast two-hybrid experiment in which we screened for interactors of PLA 2 -g and -d, we found that PLA 2 -g and -d interacted with VHA-c4, a subunit of the V-ATPase complex (see Supplemental Figure 6 online). Because PLA 2 products are known to activate V-ATPases (Palmgren and Sommarin, 1989;Pedchenko et al, 1990;Viehweger et al, 2002), the binding of these two proteins can provide a clue to the function of both PLA 2 and VHA-c4.…”
Section: Pollen Germination Is Inhibited By Treatment With Pla 2 Inhimentioning
confidence: 99%